Invitation to Letter to Editor Publication in Health Notions - David Ackah; Sanglar Polnok (Health Notions, 2020)
"Health Notions" is open to various types of scientific writings such as: original research, literature review, book review, commentary, opinion, news, case report, communication, tips, letter to editor and so on. But until now, there has never been a manuscript submission in the form of letter to editor. Therefore, through this paper we invite lecturers and researchers to send letters to editors to be published in this journal. The contents of the letter to editor for "Health Notions" are criticisms or suggestions for one of the articles that have been published in this journal. Keywords: Health Notions; letter to editor; criticisms; suggestions